Cross-cultural adaptation of the General Comfort Questionnaire to Brazilian patients with myocardial infarction - Joselice Almeida Góis; Kátia Santana Freitas; Katherine Kolcaba; Fernanda Carneiro Mussi
ABSTRACT Objective: Describe the first stages of the cross-cultural adaptation process of the General Comfort Questionnaire for myocardial infarction patients in intensive care units. Method: This is a study of qualitative and quantitative research and analysis techniques. Conceptual, item, semantic and operational equivalence was performed. Fifteen items were added to the original instrument to better represent the comfort experienced by myocardial infarction patients in intensive care units. The content validity index was applied to analyze the answers of the experts; it was considered adequate above 0.78. Results: Some changes suggested by the experts for better understanding were adopted. All items were kept, obtaining a scale of sixty-three items. In the pre-test conducted with 30 subjects, the instrument was considered adequate to the target audience. Conclusion: The adapted version of the General Comfort Questionnaire for people with myocardial infarction is adequate to the target audience.